2012
DOI: 10.1021/ja305061c
|View full text |Cite
|
Sign up to set email alerts
|

Borenium Ion Catalyzed Hydroboration of Alkenes with N-Heterocyclic Carbene-Boranes

Abstract: Treatment of alkenes such as 3-hexene, 3-octene, and 1-cyclohexyl-1-butene with the N-heterocyclic carbene-derived borane 2 and catalytic HNTf2 effects hydroboration at room temperature. With 3-hexene, surprisingly facile migration of the boron atom from C3 of the hexyl group to C2 was observed over a time scale of minutes to hours. Oxidative workup gave a mixture of alcohols containing 2-hexanol as the major product. A similar preference for the C(2) alcohol was observed after oxidative workup of the 3-octene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
107
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(112 citation statements)
references
References 49 publications
3
107
0
2
Order By: Relevance
“…Over time or upon heating the reaction mixture to 55 • C, the two multiplets converted to a single multiplet resonance at δ 3.67 ppm (see Supplementary Materials, Figure S17). Similar results were reported by Curran and co-workers, who attributed the phenomena to "chain walking" of a carbene-BH 3 adduct [19][20][21][22][23][24][25][26]. Additionally, when cis-or trans-3-hexene was introduced to 1a, compound 10 was obtained as the sole product, as indicated by the presence of a single multiplet at δ 3.67 ppm (C 6 D 6 ).…”
Section: Scheme 6 Hydroboration Of Cyclic Olefins With 1asupporting
confidence: 87%
See 1 more Smart Citation
“…Over time or upon heating the reaction mixture to 55 • C, the two multiplets converted to a single multiplet resonance at δ 3.67 ppm (see Supplementary Materials, Figure S17). Similar results were reported by Curran and co-workers, who attributed the phenomena to "chain walking" of a carbene-BH 3 adduct [19][20][21][22][23][24][25][26]. Additionally, when cis-or trans-3-hexene was introduced to 1a, compound 10 was obtained as the sole product, as indicated by the presence of a single multiplet at δ 3.67 ppm (C 6 D 6 ).…”
Section: Scheme 6 Hydroboration Of Cyclic Olefins With 1asupporting
confidence: 87%
“…In the absence of any external initiators, the NHC-BH3 adducts typically do not react with olefins. However, as shown in Scheme 1, the NHC-BH3 adducts do facilitate the hydroboration of a wide range of organic molecules at elevated temperatures and/or upon the addition of a radical initiator [19][20][21][22][23][24][25][26][27]. Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, LBH 2 X is therefore a functional equivalent of a borenium rather than a true borenium cation. More recently, this approach was extended by Vedejs, Curran, Lacôte and co-workers to the borenium equivalents (NHC)BH 2 NTf 2 and [78]. In contrast to amine borane adducts, NHCs do not dissociate from boron even under forcing conditions.…”
Section: Hydroborationmentioning
confidence: 99%
“…Building on the seminal studies by Vedejs, Curran and Lacôte, 10 we recently reported that NHC-boranes (NHC = Nheterocyclic carbene) activated with sub-stoichiometric iodine effect alkyne C-H borylation in the absence of exogenous base. 11 The turnover enabling step was proposed to involve the expected by-product from C-H borylation, HI, reacting with another equivalent of NHC⋅BR2(H) to regenerate the active boron electrophile, NHC⋅BR2(I), and H2.…”
mentioning
confidence: 99%